Pengabdian Masyarakat melalui Kegiatan Literasi Jurnalistik Digital Berbasis Nilai-nilai Kemuhammadiyahan di Desa Makamhaji: Community Service through Digital Journalism Literacy Activities Based on Muhammadiyah Values in Makamhaji Village - Septia Dinar Robbi'ah (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This community service aims to increase understanding and awareness of the community, especially the younger generation in Makamhaji Village, regarding the importance of digital journalistic literacy based on Muhammadiyah values. This activity also aims to instill an Islamic spirit, strengthen Islamic character from an early age, and develop media skills ethically and responsibly. The service was carried out in seven meetings, starting with the Aisyah Recitation activity which instills spiritual values, continued with the Ahad Pon Recitation regarding the importance of brotherhood and knowledge, as well as teaching activities at TPQ Ar-Rahman to strengthen children's character through memorizing short surahs. Digital journalism activities are carried out by providing news writing training and counseling regarding the importance of maintaining privacy on social media. The next meeting was filled with Monday Pon Recitation regarding the door to sustenance, HPT Muhammadiyah Study regarding the implementation of Eid al-Adha, and ended with follow-up activities at TPQ. All activities are integrated with an educational approach and Muhammadiyah values ​​that encourage people to become smarter, more moral and adaptive to digital developments.